Consolidation considering increasing soil column radius for dredged slurries improved by vacuum preloading method. Issue 3 (June 2022) - Liu, Sijie; Sun, Honglei; Geng, Xueyu; Cai, Yuanqiang; Shi, Li; Deng, Yongfeng; Cheng, Kang
Abstract: Soil column is often investigated in the improvement of dredged slurries. Different from the smear zone, the soil column forms gradually and has extremely low permeability. This study presents an analytical solution for soil consolidation considering the increasing radius of the soil column and time-dependent discharge capacity. Based on the solution, the influence of the radius' increase on the consolidation behavior is found significant when the soil column has low permeability and large final radius, and the increase of formation time can lead to the increase of consolidation speed and final consolidation degree. Highlights: A novel closed-form solution is obtained for the consolidation of dredged slurries improved by the vacuum preloading method considering the time-dependent soil column radius. The increase of soil column formation time leads to the increase of consolidation speed and ultimate degree. The influence of the time-dependent soil column radius is more obvious in cases with low permeability and large final radius of the soil column.